1985
DOI: 10.1002/art.1780280602
|View full text |Cite
|
Sign up to set email alerts
|

The immunoreactivity, ligand, and cell binding characteristics of rheumatoid synovial fluid fibronectin

Abstract: Fibronectin promotes macrophage adherence and expression of Fc receptors, is chemotactic for fibroblasts, and is an opsonin for fibrin and denatured collagen. These properties suggest a role for fibronectin in the modulation of joint inflammation. Since structural modification of the fibronectin molecule has been shown to result in loss or de novo acquisition of opsonic and chemotactic activity, we determined the functional and immunochemical properties of fibronectin isolated from the inflamed joint. Eighty‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…As demonstrated here, Wnt-1-like signaling up-regulates the synthesis of the cell adhesion molecule fibronectin in RA FLS. Fibronectin expression is high in the synovial tissues and synovial fluids of RA patients (35,36). Taken together with earlier data, these results suggest that the high fibronectin levels in RA are partly attributable to augmented Wnt-1-like activity in RA FLS.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…As demonstrated here, Wnt-1-like signaling up-regulates the synthesis of the cell adhesion molecule fibronectin in RA FLS. Fibronectin expression is high in the synovial tissues and synovial fluids of RA patients (35,36). Taken together with earlier data, these results suggest that the high fibronectin levels in RA are partly attributable to augmented Wnt-1-like activity in RA FLS.…”
Section: Discussionsupporting
confidence: 81%
“…Fibronectin promotes the survival of mesenchymal cells by localizing growth factors and by stimulating integrin-mediated signaling pathways (36,41). Consistent with this knowledge, confluent nonproliferating cultures of RA FLS (passage 6), which overexpressed fibronectin, survived better than normal fibroblasts (same passage) when the 10% FBS culture medium (complete medium) was replaced by serum-free medium, conditions in which growth factor concentrations are expected to be low ( Figure 9A).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Degraded matrix conveys messages that are different from those normally conveyed by an intact or stable matrix, and the degradation increases with the severity of the disease. In periodontal disease and arthritis, FN fragments are most abundant in the most diseased sites (6,(25)(26)(27)(28)(29)(30). Previously, we found that a proteolytic 40-kDa fragment of FN associated with the most advanced disease also induced apoptosis of periodontal ligament fibroblasts in vitro by down-regulating p53 and c-Myc (6, 7).…”
Section: Discussionmentioning
confidence: 99%